Beyond Traditional Bureaucracy: Building Agile Public Organizations in an Era of Disruption - Iskandar, Didik (ASHA Publishing, 2025)
This study examines the transformation of public organizations from traditional bureaucratic structures to agile organizational models in response to digital disruption and evolving citizen expectations. Employing a sequential explanatory mixed-methods design, the research analyzed 45 public organizations across 12 administrative regions and six sectoral domains through quantitative surveys (n=127 respondents) and qualitative semi-structured interviews over a 24-month period. Results demonstrate that digital disruption serves as the primary transformation catalyst (78% of cases), with pilot-driven implementation strategies achieving significantly superior success rates (85.7%) compared to comprehensive redesign approaches (33.3%). Cross-sectoral analysis reveals substantial variation in transformation effectiveness, with service-oriented sectors (health: 89.3%, education: 87.1%) significantly outperforming traditional bureaucratic domains (regulatory: 58.7%, infrastructure: 54.2%). (F (5,39) = 12.47, p < 0.001, η² = 0.615). Post-transformation outcomes show statistically significant improvements in organizational performance, including a 45% reduction in response times and a 30% increase in citizen satisfaction scores, with large effect sizes (Cohen's d > 1.3) indicating practical significance. The findings suggest that successful agile transformation in public organizations requires adaptation rather than direct transplantation of private sector models, with sustainable change achieved through hybrid approaches that balance agile principles with democratic accountability requirements, establishing an empirical foundation for agile governance models in contemporary public administration.